Enhancing Organizational Memory Through Virtual Memoryscapes: Does It Work? - Mastrogiorgio, Antonio; Zaninotto, Francesca; Maggi, Francesca; Ricciardi, Emiliano; Lattanzi, Nicola; Malizia, Andrea P. (Frontiers in Psychology, 2021)
Enhancing cognitive memory through virtual reality represents an issue, that has never been investigated in organizational settings. Here, we compared a virtual memoryscape (treatment) – an immersive virtual environment used by subjects as a shared memory tool based on spatial navigation – with respect to the traditional individual-specific mnemonic tool based on the “method of loci” (control). A memory task characterized by high ecological validity was administered to 82 subjects employed by large banking group. Memory recall was measured, for both groups, immediately after the task (Phase 1) and one week later (Phase 2). Results show that (i) in Phase 1, the method of loci was more efficient in terms of recalling information than the to the virtual memoryscape; (ii) in Phase 2, there was no difference. Compared to the method of loci, the virtual memoryscape presents the advantages – relevant for organizations – of being collective, controllable, dynamic, and non-manipulable.